2017
DOI: 10.18632/oncotarget.19574
|View full text |Cite
|
Sign up to set email alerts
|

The response of the Oxford classification to steroid in IgA nephropathy: a systematic review and meta-analysis

Abstract: BackgroundThe present review is aimed to evaluate the correlation between pathological features and the response to steroid in the patients with IgA nephropathy according to the Oxford classification, mesangial hypercellularity (M), endocapillary hypercellularity (E), segmental glomerulosclerosis (S), tubular atrophy and interstitial fibrosis (T).MethodsWe searched Chinese Biomedical Database, EMBASE, Cochrane Library, PubMed and MEDLINE with all spellings of “IgA nephropathy”, “Oxford Classification”, and “st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
(34 reference statements)
1
17
0
Order By: Relevance
“…Other outcomes, such as proteinuria remission, were not obtained, and these outcomes may have been associated with the MEST-C scores. The use of treatment agents, such as antihypertensive drugs and steroids, was not considered in multivariate models because of missing values, although these agents have been known to affect the predictability of pathological parameters [15,32]. The results from Korean patients may have limited applicability to Caucasian patients; thus, a current pooled analysis with results from both ethnics may be more generalizable than results from Korean patients alone.…”
Section: Discussionmentioning
confidence: 99%
“…Other outcomes, such as proteinuria remission, were not obtained, and these outcomes may have been associated with the MEST-C scores. The use of treatment agents, such as antihypertensive drugs and steroids, was not considered in multivariate models because of missing values, although these agents have been known to affect the predictability of pathological parameters [15,32]. The results from Korean patients may have limited applicability to Caucasian patients; thus, a current pooled analysis with results from both ethnics may be more generalizable than results from Korean patients alone.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with M1, S1, and T1/2 were resistant to steroid/immunosuppressive therapy, and E1 is a better response to steroid therapy than T1/2. 36 …”
Section: Methodsmentioning
confidence: 99%
“…Intensive immunosuppression [corticosteroid with cyclophosphamide (CTX) or azathioprine] is reserved for patients with crescents in more than half of the glomeruli and rapidly deteriorating renal function [8]. A meta-analysis has shown that IgAN patients with more serious pathological features may be more resistant to steroid therapy than slight ones according to the earlier outlined Oxford classification system [9]. However, the benefits of systemic immunosuppression have been questioned in recently completed trials.…”
Section: Latest Kidney Disease: Improving Global Outcomes (Kdigo) CLImentioning
confidence: 99%